Electrocortical correlates of temperament - Tatalović Vorkapić, Sanja (Array, 2013)
Numerous research studies have tried to understand the brain-behaviour relationship applying electrophysiological investigations of human personality. As a result, respectable number of explorations was done on the field of biological bases of extraversion and very few on the relationship between temperament and evoked brain potentials. In addition, even though Strelau considered temperament traits were primarily biologically based, there were a small number of psychophysiological studies within the field of temperament. Taken altogether, the main aim of this study was to investigate the relationship between three temperament dimensions: strength of excitation, strength of inhibition and mobility measured by Pavlov’s Temperament Survey (PTS), and amplitudes and latencies of evoked brain potentials (N1, P2, N2, P3 & SW) measured by a simple visual oddball paradigm in two blocks. The participants were female psychology students (N=54) with mean age of 20. Signiﬁcant positive correlations were determined between amplitudes of N1-P2-N2-P3 components and strength of excitation and mobility in the ﬁrst and second block, mostly on parietal electrodes, as well as signiﬁcant negative correlations of amplitudes of N1-P2-N2-P3 components and strength of inhibition. Expected signiﬁcant negative correlation between mobility and EP-latencies was not found in this study. Considering measurement limitations in this research, important future study directions have been given. Various models of personality, specific information processing and different reactions to the easy/hard tasks used in research represent rather signiﬁcant moderating factors of the relationship between temperament and evoked potentials, what should be taken into consideration in the future studies.